J. Christoph Amberger’s hot trading secrets : - Amberger, J. Christoph (Wiley, 2006)
In Hot Trading Secrets, Amberger reveals: The predictive power of Dynamic Market Theory; Why you need to cast a wide net; How to own the future; Insider information" is not illegal—and why you must use it; How to trade extreme volatility